Four days in Hitler's Germany : Mackenzie King's mission to avert a Second World War - Teigrob, Robert 1966- (University of Toronto Press, 2019)
"In 1937, Canadian Prime Minister Mackenzie King travelled to Nazi Germany in an attempt to prevent a war that, to many observers, seemed inevitable. The men King communed with in Berlin, including Adolf Hitler, assured him of the Nazi regime's peaceful intentions, and King not only found their pledges sincere, but even hoped for lifelong personal friendships with many of the regime's top officials. Four Days in Hitler's Germany is a clearly written and engaging story that reveals why King believed that the greatest threat to peace would come from those individuals who intended to thwart the Nazi agenda, which as King saw it, was concerned primarily with justifiable German territorial and diplomatic readjustments. Mackenzie King was certainly not alone in misreading the omens in the 1930s, but it would be difficult to find a democratic leader who missed the mark by a wider margin. This book seeks to explain the sources and outcomes of King's misperceptions and diplomatic failures, and follows him as he returns to Germany to tour the appalling aftermath of the very war he had tried to prevent."--